Multinational companies: Can they foster well-being in the eyes of the poor? Results from an empirical case study - Harald Strotmann; Jürgen Volkert; Melinda Schmidt (International Journal of Corporate Social Responsibility (JCSR), 2019)
Corporate Social Responsibility (CSR) is supposed to benefit corporations but as well to foster the well-being of individuals, communities and society. However, there is still a lack of reliable evaluation results of CSR's effectiveness and efficiency. In addition, development researchers complain that, despite CSR's claim and implicit hypothesis of mutually beneficial impacts, business studies, notably when addressing CSR impacts on the poor, do not sufficiently understand and take account of well-being effects in the eyes of the poor. The paper at hand empirically analyses the effects of a CSR strategy on the reported well-being of poor villagers in rural India. For the case of the Bayer Crop Science Model Village Project (MVP) and based upon quantitative data from a panel survey of about 2300 villagers living in some 1000 households, both descriptive analyses and multivariate analyses in this paper indicate that the activities initiated within the Model Village Project have c. p. contributed to a significant improvement of the villagers' reported well-being from 2011 until 2014. This is confirmed firstly by comparing the well-being development in two model villages in which Bayer undertook a variety of initiatives with the corresponding well-being development in two control villages in which no activities were started. Secondly, this conclusion is also underlined by comparisons of reported well-being changes of MVP participants and non-participants within the model villages.
Keywords: I30; Q12; M14; O15; 650; Capability approach; Corporate social responsibility; India; Poverty; Well-being